Mycobacterium tuberculosis and Dual M. tuberculosis/M. bovis Infection as the Cause of Tuberculosis in a Gorilla and a Lioness, Respectively, in Ibadan Zoo, Nigeria - Aina Adeogun; Olutayo Omobowale; Chiaka Owuamanam; Olugbenga Alaka; Victor Taiwo; Dick van Soolingen; Simeon Cadmus (Case Reports in Veterinary Medicine)
Tuberculosis (TB) in zoo animals is an important public health problem in places where it occurs. This is even very important in countries where there is little public health awareness about the disease; thus confined animals in the zoo can be infected directly or indirectly by infected humans and vice versa. In Nigeria, the problem of TB is a major concern among both humans and cattle. Here, we present cases of Mycobacterium tuberculosis and M. tuberculosis/M. bovis infections in a female gorilla and a lioness, respectively, in a zoo in Ibadan, Nigeria. These cases were confirmed after bacteriological examinations and DNA from granulomatous lesions of the animals’ carcasses were subjected to the Hain and spoligotyping techniques. Our findings reveal the first documented report of TB infections in a gorilla and a lioness in zoo animals in Nigeria. The public health risks of tuberculosis in zoological settings are therefore reemphasized.